Layered CuI: a path to 2D p-type transparent conducting materials - Seifert, Michael; Kawashima, Moemi; Roedl, Claudia; Botti, Silvana (Journal of Materials Chemistry C, 2021)
Zinc blende copper iodide, a p-type semiconductor that is transparent in the visible spectral range, has attracted growing attention as a promising material for transparent electronics. While the zinc blende γ-phase is the most studied, the semiconducting layered β-phase deserves more consideration being potentially suited for 2D applications. Here, we present anab initiostudy of these two phases of CuI in the framework of density functional theory. We first discuss structural and elastic properties, and for β-CuI we calculate the exfoliation energy. The comparison of electronic band structures and optical properties shows that small light-hole effective masses and large band gaps are common characteristics of the two considered phases. These properties are also preserved in the β-CuI monolayer and point to the possibility of obtaining a high-performance transparent monolayer conductor for application in 2D electronics.
CRIS-Team Scopus Importer:2023-04-20